Do ESG and Earnings Management Influence Audit Opinions? Evidence from Indonesia Mining Sector - Rivaldo, M.Untung; Utaminingsih, Nanik Sri (Economics, Business, Accounting & Society Review, 2026)
This study examines how non-financial and financial signals influence the issuance of modified audit opinions in the Indonesian mining sector. In recent years, auditors have increasingly incorporated sustainability-related considerations into audit risk assessments, particularly in industries characterized by high environmental and regulatory risk. This research aims to investigate whether Environmental, Social, and Governance (ESG) performance and earnings management affect auditors’ decisions to issue modified audit opinions. Using a quantitative causal research design, the study analyzes mining companies listed on the Indonesia Stock Exchange that are included in the Katadata ESG Index during the observation period. Modified audit opinion serves as the dependent variable, while ESG performance and discretionary accrual–based earnings management are the main independent variables, with firm size and leverage included as control variables. Given the relatively low occurrence of modified audit opinions, the empirical analysis employs Firth Logistic Regression to address rare-event bias. The results show that ESG performance has a significant negative association with the likelihood of receiving a modified audit opinion, indicating that stronger sustainability and governance practices are perceived by auditors as signals of lower audit risk. In coxntrast, earnings management does not exhibit a significant effect on audit opinion outcomes. These findings suggest that in high-risk industries such as mining, auditors place greater reliance on credible non-financial signals related to sustainability and governance than on accrual-based financial signals when forming audit opinions.